EXPERIMENTAL CONSTRUCTION DEVELOPMENT OF THE DEVICE FOR CLEANING COTTON FROM SMALL IMPURITIES (E Global Congress, 2025)
In the article, the working scheme and experimental design of the device for cleaning cotton from small impurities have been developed. In this study, the improved device was tested for its efficiency and energy efficiency, and corresponding results were obtained. This study focuses on optimizing the cleaning efficiency of cotton ginning by developing a device that reduces mechanical damage while improving the quality of the fiber. The experimental device includes a continuous slotted mesh surface and a pile drum system, which significantly enhances impurity removal.